Cuenca in these fifteen years - López Avilés, Monika (Universidad de Cuenca, 2015)
We experienced mixed feelings at the start of our exhibition. On the one hand we have the enthusiasm of having to express some thoughts from our profession, the preservation of Heritage Material of the city of Cuenca, that we just started from the date of the Declaration, in 1999. On the other hand, we feel a kind of bad impression, because apparently any  investigative effort on the subject does not have the range expected in the city.Keywords: Historical and heritage areas, inventories.